IMPLEMENTASI PROGRAM BANTUAN LANGSUNG TUNAI (BLT) BAGI MASYARAKAT MISKIN DI DESA LARINGGI KABUPATEN SOPPENG - Tsania, Nur Fitria; Setiawati, Budi; Arfah, Sitti Rahmawati (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2023)
This study aims to determine the implementation of the cash transfer program in Laringgi village. The type of research used is a qualitative research method with a descriptive type of research. The BLT program aims to reduce poverty. Data collection techniques use observation, interviews, and documentation. The results of the study The implementation of the direct cash assistance program (BLT) in Laringgi Village, consists of four aspects, namely (1) Communication, divided into three, namely: First, the transmission/channel of communication from the village government has been effective in distributing direct cash assistance (BLT), the second is clarity of socialization. has been evenly distributed while in the third the consistency is still lacking. (2) The disposition/attitude is quite good, the people who receive the assistance are very happy. (3) The resources consist of human resources that are quite good in the direct cash assistance program (BLT), the facilities and infrastructure are adequate. (4) Bureaucratic structure, divided into two, namely SOP and Fragmentation, both of which are good in the direct cash assistance program